The effects of physical classroom environment on the achievement of students taking intensive Advanced English II, group o5, at the Foreign Language Department, School of arts and Sciences of the University of El Salvador, semester I, 2020 - Palacios Regalado, Roberto Antonio (2024)
The physical classroom environment has been investigated by many researchers, and the University of El Salvador has many problems related to it due to the critical conditions of the classrooms, and the researcher decided to investigate in order to know if students were affected by it or not. The students who were taking Intensive Advanced English II, group 05, semester I, were selected for this research because the classrooms are in terrible conditions as stated above. It was necessary to identify the most common problems, negative or positive consequences, and how physical classroom environment can affect the students’ achievement. For this project, 27 students composed the sample to gather all the data, and surveys, interviews, and an ethnographic observation were used to go deeper into this research. Finally, after all the techniques and instruments were used, it was found that students and teachers ask for help to improve the physical classroom environment; however, most of the students are positive to achieve their academic goals, and they are not getting strongly affected by the physical classroom environment on this researched group. Key Words: Condition of the Classrooms ; Common classroom problems ; Classroom environment ; Students' achievement ; Students affected.